Early Childhood Caries Among Overweight and Obese Children - Anggun Rafisa; Felisha Febriane Balafif; Nuroh Najmi; Faisal Kuswandani (Sean Institute, 2023)
Dental caries and obesity are both global public health issues that can have an impact on overall systemic health. Despite numerous studies investigating the link between dental caries and obesity, the findings remain inconclusive. This review aimed to determine the relationship between overweight, obese and ECC, as well as the impact of other potential risk factors. Research articles were searched using electronic databases such as Pubmed and Scopus. The selection of studies was following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocols. The initial phase of searching for articles in databases yielded 1176 results. There were twenty-three articles that received full-text appraisals, and fourteen studies were eliminated for not meeting the eligibility criteria. Finally, the study included nine articles. Only one of the nine articles considered in this review was a cohort study. The years of publishing range from 2019 to 2023. The majority of the study settings (n=5) were in high-income countries. Five of the studies reviewed found no association between overweight or obesity and ECC, whereas four identified a significant association. Based on the findings of this review, the association between overweight, obesity, and ECC appears undetermined. The differences in the findings of the studies included in this review could be attributed to the various BMI indicators employed to define the nutritional status of children. Other risk factors such as family socioeconomic status, parental educational level, and parental awareness of oral hygiene and dental visits may influence the association between overweight, obesity, and ECC.